2015
DOI: 10.1128/iai.00401-15
|View full text |Cite|
|
Sign up to set email alerts
|

Staphlyococcus aureus Phenol-Soluble Modulins Stimulate the Release of Proinflammatory Cytokines from Keratinocytes and Are Required for Induction of Skin Inflammation

Abstract: Staphylococcus aureus is a human commensal that colonizes the skin. While it is normally innocuous, it has strong associations with atopic dermatitis pathogenesis and has become the leading cause of skin and soft tissue infections in the United States. The factors that dictate the role of S. aureus in disease are still being determined. In this work, we utilized primary keratinocyte culture and an epidermal murine colonization model to investigate the role of S. aureus phenol-soluble modulins (PSMs) in proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 48 publications
3
70
1
Order By: Relevance
“…Furthermore, cell lysis may also explain the release of IL-8, as the PSM concentrations used in those experiments were in the cytolytic range (12). Similarly, the stimulation of PSM-induced IL-1␤ and IL-18 release from human keratinocytes, highly specialized epithelial cells, was also likely associated with cell lysis (15). Treatment of bovine PS cells with PSM␣3 at 2 g/ml for 8 h resulted in increased interleukin expression in the absence of a cytotoxic effect (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, cell lysis may also explain the release of IL-8, as the PSM concentrations used in those experiments were in the cytolytic range (12). Similarly, the stimulation of PSM-induced IL-1␤ and IL-18 release from human keratinocytes, highly specialized epithelial cells, was also likely associated with cell lysis (15). Treatment of bovine PS cells with PSM␣3 at 2 g/ml for 8 h resulted in increased interleukin expression in the absence of a cytotoxic effect (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, PSMs are responsible for modulation of cytokine secretion. It was demonstrated that PSMs induce the release of IL-8 from neutrophils (13) and IL-18 from human keratinocytes, likely through the lytic release (15). In contrast, simultaneous treatment of dendritic cells with S. aureus cell lysate and PSM␣ inhibited the secretion of TNF, IL-6, and IL-12, whereas the secretion of the anti-inflammatory cytokine IL-10 was increased (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Protein A can induce TNF-α production in keratinocytes in a non-toxic manner [64]. Finally, S. aureus-secreted PSMs are also known to increase inflammation in keratinocytes [69]. Although much is known of the virulence factors discussed above, more are still being discovered.…”
Section: S Aureus Virulence Factors In Ad Severitymentioning
confidence: 98%
“…4F). Recently, staphylococcal PSMs have been implicated in skin and soft tissue infection (SSTI) (28)(29)(30) and have shown significantly higher levels of expression in methicillin-resistant S. aureus (MRSA) strains isolated from SSTIs. These observations imply that the small ORFs detected in the present study might be candidates that contribute to in vivo abscess formation.…”
Section: Resultsmentioning
confidence: 99%